The Impact of Perceived Supervisor Support, Work Life Balance and Work Engagement in Controlling Turnover Intention in a Pharmaceutical Manufacturing Company - , Tjhia Lian Nie; Harjono, Saebani; Purba, Sylvia Diana; Sulistyaningsih, Endang (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
This research aims to determine the effect of perceived supervisor support on turnover intention which is mediated by work life balance and work engagement. This research was conducted at a pharmaceutical manufacturing company in Cikarang, West Java using a non-probability sampling technique, namely purposive sampling. The author distributed an online questionnaire to every worker with permanent employee status with a minimum work period of 1 (one) year to 107 workers. The data analysis method uses the PROCESS Hayes macro bootstrapping method in SPSS. The research results show that perceived supervisor support does not have a significant effect on turnover intention, but work life balance and work engagement fully mediate the influence of perceived supervisor support on turnover intention